Opioid, methamphetamine, and polysubstance use: perinatal outcomes for the mother and infant - Wouldes, Trecia A.; Lester, Barry M. (Frontiers in Pediatrics, 2023)
The escalation in opioid pain relief (OPR) medications, heroin and fentanyl, has led to an increased use during pregnancy and a public health crisis. Methamphetamine use in women of childbearing age has now eclipsed the use of cocaine and other stimulants globally. Recent reports have shown increases in methamphetamine are selective to opioid use, particularly in rural regions in the US. This report compares the extent of our knowledge of the perinatal outcomes of OPRs, heroin, fentanyl, two long-acting substances used in the treatment of opioid use disorders (buprenorphine and methadone), and methamphetamine. The methodological limitations of the current research are examined, and two important initiatives that will address these limitations are reviewed. Current knowledge of the perinatal effects of short-acting opioids, OPRs, heroin, and fentanyl, is scarce. Most of what we know about the perinatal effects of opioids comes from research on the long-acting opioid agonist drugs used in the treatment of OUDs, methadone and buprenorphine. Both have better perinatal outcomes for the mother and newborn than heroin, but the uptake of these opioid substitution programs is poor (<50%). Current research on perinatal outcomes of methamphetamine is limited to retrospective epidemiological studies, chart reviews, one study from a treatment center in Hawaii, and the US and NZ cross-cultural infant Development, Environment And Lifestyle IDEAL studies. Characteristics of pregnant individuals in both opioid and MA studies were associated with poor maternal health, higher rates of mental illness, trauma, and poverty. Infant outcomes that differed between opioid and MA exposure included variations in neurobehavior at birth which could complicate the diagnosis and treatment of neonatal opioid withdrawal (NOWs). Given the complexity of OUDs in pregnant individuals and the increasing co-use of these opioids with MA, large studies are needed. These studies need to address the many confounders to perinatal outcomes and employ neurodevelopmental markers at birth that can help predict long-term neurodevelopmental outcomes. Two US initiatives that can provide critical research and treatment answers to this public health crisis are the US Environmental influences on Child Health Outcomes (ECHO) program and the Medication for Opioid Use Disorder During Pregnancy Network (MAT-LINK).